The Metaverse and Marketing: How Virtual Worlds are Changing The Way We Sell and Consume - Panjaitan, Feliks Anggia Binsar Kristian (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Metaverse offers innovative new opportunities for companies in marketing strategies, including in the cosmetics, arts, cultural heritage and banking industries. This research aims to compare the effectiveness of immersive marketing strategies in the Metaverse with conventional digital marketing strategies in building brand loyalty. The research method involves systematic literature observations using leading international databases such as Scopus, Web of Science, and PubMed, using inclusion and exclusion criteria and the PRISMA method. The research results show that immersive marketing in the Metaverse significantly increases consumer engagement and interaction compared to conventional digital marketing, albeit at a higher cost. The implications of this research highlight the importance of combining immersive and conventional marketing strategies to maximize consumer engagement and loyalty in the ever-evolving digital era.